MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER PADA MATA PELAJARANMATEMATIKA DI KELAS V - JUNIKO ESRA TARIGAN; ANANDA AYU MUTIARA (JURNAL CURERE, 2019)
ANANDA AYU MUTIARA, NPM 1305030167 “Improving of Student Learning Outcomes by Cooperative Learning Model Numbered Head Together Type of Math Story Studies in V Grade Class National Elementary School 066668 of Medan Johor 2016/2017 in years”. This research was held aims to fix learning and increase students learning output by cooperative learning model Numbered Head Together in type at math studies of common fraction distribution compare in mix fractional material. The main problems in this research so down exam outcomes of students in math studies indeed. The type of research is in classroom based action research. The subjects of this are who they has member of class V grade in national elementary school students 066668 Medan Johor being at 2016/2017 years entry within 40 students in a class and got to stand by 19 male students and 21 female students in are. The step of this research was due to two sessional that are part 1 and part 2 in a while. Tools of data collected had exam tests in essay form in a much 4 essay. By data of result outcomes within observation found by implementation of learning, teacher activity conducted growing up in 21,38% came from 59,69% score to 72,45% . Students activity told to growing 29,41% came from 68 to 88 in value, to individual completed when they should got 70 point in KKM, in classical look up in 29,63% from percentage of 67,5% to 87,5% and point of mean got up from 69,43 to 74,45. The conclusion by this research told to by the implemented of studies conducted the great criteria and outcomes studies had advance applied after by cooperative learning model in Numbered Head Together typed at the math stories studies within common fraction distribution compare in mix fractional material in V grade of class national elementary school 066668 Medan Johor 2016/2017 in years.